Identifikasi Tumbuhan Paku di Hutan Penggaron Kecamatan Ungaran Kabupaten Semarang - Abadiyah, Auliya Saadatul; Wahidah, Baiq Farhatul; Hariz, Anif Rizqianti (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2019)
Indonesia has a strategic geographical area with high biodiversity potential, it is located in the equatorial region which causes Indonesia have a tropical climate. The biodiversity of forests in Indonesia includes ferns. Nail plants can be found with a variety of types in various environments, especially in shady areas such as forests. Ferns are plants that have an important role in the forest ecosystem as a source of germplasm. Besides that, ferns also have the potential as a source of food and medicine for the Penggaron Forest, or who is familiarly called the Penggaron Tourism Area, is one of the natural tourism objects located in Semarang Regency, precisely in Susukan Village, Ungaran District, Semarang Regency. This study aims to identify the species of ferns in the Penggaron Forest. Data collection techniques used in identifying plant ferns are: 1) orientation and exploration of locations; 2) gathering ferns by exploring along the main road to the location of the campsite; 3) record and document the ferns found in the field. The results of the identification of ferns in the Penggaron Forest there are 2 families of ferns consisting of 23 species of plants. The Scizaeaceae family consists of 4 types of plants namely Lygodium flexuosum, Lygodium japonicum, Lygodium palmatum, and Lygodium circinatum. While the Polypodiaceae family consists of 19 types namely Nephrolepis hirsutula, Nephrolepis biserrata, Dryopteris scotii, Adiantum, Adiantum raddianum, Mickelopteris cordata, Pteris ensiformis, Pteris asperula, Pteris biaurita, Pteris vittata, Adiantum, Adiantum raddianum, Mickelopteris cordata, Pteris ensiformis, Pteris asperula, Pteris biaurita, Pteris vittata, Adiantum, Adiantum raddianum, Mickelopteris cordata, Pteris ensiformis, Pteris asperula, Pteris biaurita, Pteris vittata crenata, Tectaria angulata, Tectaria maingayi, Tectaria heracleifolia, Pleocnemia irregularis.